Research advances on mechanisms and preventions of the medicinal plants’ continuous cropping obstacles from the perspective of rhizosphere microecology - QU Yuting; ZHANG Qianqian; YU Yefei; Sayikal DUYXANALE; CAI Linlin; ZHANG Sujiong; LI Yongfu; LI Yongchun (浙江大学学报. 农业与生命科学版)
The ability of the rhizosphere micro-ecosystem to resist pathogenic microorganisms declined, induced by different dose-effect relations in the “plant-soil-microbe” system, culminating in yield loss and quality deterioration. This paper reviewed the causes of continuous cropping obstacles of medicinal plants and the strategies to mitigate these obstacles from the perspective of rhizosphere microecology. Then we summarized the existing problems in the field and recommended directions for future research. Continuous cropping leads to changes in the complicated interactions between the medicinal plant’s roots and their exudates, as well as the microbial population and community structure, which in turn leads to the imbalance of the original rhizosphere micro-ecosystem and benefits soil-borne diseases. Therefore, based on the interactions between medicinal plants and the rhizosphere environment, this paper proposed various mitigation strategies, including plant breeding, soil microbial community assembly and so on. These strategies could serve to maintain the balance of the soil ecosystem, and consequently plant health, and ultimately improve the yield and quality of medicinal plants. This study recommended that researchers who worked on the continuous cropping obstacles focused on the interactions and mechanisms among plant-soil-microbe which are mediated by the plant-pathogen competition, to provide guidance for the effective management of continuous cropping control and the healthy development of medicinal plants in the future.